An Investigation of Peace Components in the Reading Textbooks of Elementary Schools - Babak Shamshiri; Jaber Eftekhari (Iranian Evolutionary Educational Psychology Journal, 2021)
The purpose of this study was to examine the components of peace in the text of elementary school reading textbooks. The method used in this research was exploratory sequential mixed methods design. In this way, after identifying the components of peace in the qualitative section as criteria for analysis and determining the paragraphs of each lesson as a unit of analysis, the method of William Rumi was used in the quantitative section to analyze the content of the text of the reading textbooks. Also, in the qualitative part, the audit trail method was used to measure credibility. In addition, in the quantitative part, the inter-rater reliability was calculated .83, which was significant at the level of .001. The results in the quantitative part showed that the level of attention of each book to the components of peace is lower than the average (involvement coefficient is less than 1). Accordingly, the books need fundamental revisions regarding attendance to peace and its basic components. In addition, the level of attention of the books to the components is not balanced, and among these, the component of compassion has the highest frequency and justice has the lowest frequency.